Life Skills Development Program for Orphans in Medan - Andi; Siregar, Izuddinsyah; Sitepu, Muhammad Rizal; Rinaldi, Muammar; Fahrizi, Haikal Al (Outline Publisher, 2025)
The Life Skills Development Program for Orphans in Medan was implemented as an effort to increase the capacity, independence, and future preparedness of children who are in vulnerable situations due to a lack of nuclear family support. This activity focuses on providing soft skills and hard skills training through a Participatory Action Program (PAP) approach that actively involves participants in the learning process. Soft skills training includes self-management, effective communication, teamwork, and critical thinking skills, while hard skills training emphasizes digital literacy, creative skills, and basic entrepreneurship. Evaluation of the activity was carried out through pre- and post-tests, behavioral observations, mini-project assessments, and participant satisfaction questionnaires. The results of the activity showed a significant increase in participants' knowledge, self-confidence, communication skills, creativity, and technical skills. The program also produced training modules that can be used continuously by orphanages. Thus, this program has proven effective in helping orphans develop relevant life skills that can be applied in everyday life and serve as an important foundation for future economic and social independence